Traditional tensions and contemporary coalitions: a confluence of historic geopolitical friction, Cold War alliances and relations between Germany and its neighbours from 1945 to 1991 - Tan, Douglas Han Long (Nanyang Technological University, 2023)
By virtue of geostrategic positioning as well as both historic and contemporary political and economic influence, there are perhaps few countries in Europe which possess as much, if not more, geopolitical significance as Germany. In particular, Germany’s historic geopolitical eminence on the continent also possesses much complex and intricate links with its diplomatic relations and engagements with its neighbours during the 20th century. The two world wars and the Cold War which followed shortly after certainly had much impacts on the ties between Germany and such countries as the UK, France, Poland and Czechoslovakia, especially exemplified by abject relations between Germany and the four aforementioned countries from 1900 to 1945 and the subsequent division of Germany and Europe after WWII. However, as the Cold War’s manifestation of strict bipolarity induced countries on both sides of the Iron Curtain to unite and cooperate against the perceived enemy on the other side, how did the two Germanies and its respective new allies in either superpower camp work together despite their troubled past? This query lies at the core of this paper’s development and resonates strongly with attempts to understand how such new alliances were likely affected by their historic animosities and tensions.